Critical tourism pedagogies: Exploring the potential through food. (November 2017) - Mair, Heather; Sumner, Jennifer
AbstractŠ: Tourism scholars and educators are challenging the long-standing assumption that education should meet the needs of industry and have begun asking what can be done to help students think more broadly and critically about the tourism encounter. Less considered, however, is the role and potential of tourism as (critical) public pedagogy. We move 'beyond' the classroom to assess tourism's broader role in the development of critical inquiry. This paper first illuminates the public, pedagogical role of tourism, arguing that tourism is inherently (and often uncritically) pedagogical. Drawing on the works of key critical pedagogical thinkers, we explore the ways in which tourism could engender critical inquiry. Using food as a platform for this exploration, we offer examples of how critical tourism pedagogies could operate in this context. We conclude by identifying opportunities to situate and evaluate other tourism experiences in regards to how they could encourage critical tourism pedagogies.